A última estação do trem: percurso da história da educação protestante em Lavras - Lima, Maria Camila (2015)
This study lies in the field of History of Educational Institutions and its main purpose is to describe and analyze the headquartersof the Protestant educational thought occurred in the early twentieth century, characterized by the Presbyterian Institute Gammon. The city of Lavras received the Protestant ideas, incorporating educational practices to the evangelization process. Gammon Institute actively participated in educational practices in the twentieth century, becoming a regional reference in the city. It is a research that has as a methodology document analysis, which is made a systematization and analysis of files available in memorial of that institute. One time frame is required: back to the early years of the Republic Brazil, in 1892,during which the Presbyterian missionaries settled in Lavras, creating the first official course in Minas Gerais Presbyterian Church of South Mission of the United States. The deadline set refers to the year 1938, in which the Agricultural School of Lavras happens to be named Escola Superior de Agricultura de Lavras (ESCOLA SUPERIOR DE AGRICULTURA DE LAVRAS). The sources used for the research were found in documents (newspapers, letters, Minutes, reports, school listing and others) found in Pro-memory in the Presbyterian Institute Gammon.